Physical and Thermal Properties of Novel Native Andean Natural Fibers - Mori S. (2021)
This work was supported by the Cienciactiva -?FONDECYT, Per? [117-2016]. This paper was written in the context of the project: ?Estudio comparativo del potencial de fibras naturales end?micas del Per? para su uso como refuerzo en materiales compuestos laminados? founded by the Consejo Nacional de Ciencia, Tecnolog?a e Innovaci?n Tecnol?gica (CONCYTEC) under the contract number N? 117-2016-FONDECYT. The authors of this paper appreciate the financial support from the Peruvian Government.